Preliminary experimental evaluation of a novel loudspeaker featuring magnetorheological fluid surround absorber - Endra Dwi Purnomo; Ubaidillah Ubaidillah; Fitrian Imaduddin; Iwan Yahya; Saiful Amri Mazlan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A novel design of magnetorheological fluids (MRF) based surround device in a loudspeaker system was studied in this article. The main objective of this research is to design a new surround device of the loudspeaker that can be easily controlled its damping. Therefore, it was predicted that the audio pressure level on the loudspeaker could be easily manipulated at a different sound source by applying a certain magnetic field. This function could not be reached using one conventional speaker system. Firstly, a set of an electromagnetic device containing MRF was designed to replace the conventional rubber surround. The magnetic circuit was then evaluated using the finite element method magnetics to study the flux distribution in the MRF area. The current was varied from 0.25 to 0.75 A by an interval of 0.25 A. The magnetic flux resulted from the simulation was then logged and used as the based value for predicting the change of shear yield stress. The base properties of the shear yield stress of the MRF against the magnetic flux was obtained from previous experimental result. Therefore, it was hopefully the prediction could be closed to the real system. Based on the simulation result, the shear yield stress varied from 43 to 49 Mpa or about 15 % increment. A simple experimental work was carried out. By applying particular direct current into the coil, the sound quality generated by the loudspeaker shows different values. Based on the preliminary experiment, the level of decibel decreased about 3 dB as the application of magnetic fields. The idea has been proven in this preliminary experimental evaluation.